A sustainable production of natural hydraulic lime mortars through bio-amendment. (18th July 2022) - García-González, Julia; Faria, Paulina; Pereira, Alice S.; Lemos, Paulo C.; Juan-Valdés, Andrés
Highlights: A bioproduct from fermentation of biodiesel's crude glycerol replaced the mixing water on NHL mortars. The influence of being sonicated or not and the concentration of the bioproduct were assessed. The waste-based bioproducts had a positive effect on workability and mechanical performance. The bioproducts reduced mortarś water absorption, therefore improving durability. They may be a promising alternative to petrochemical additions to produce sustainable NHL mortars. Abstract: This article examined the effect of a bioproduct suspension obtained from fermentation of biodiesel's crude glycerol when used to formulate natural hydraulic lime mortars, as a fluid replacing the mixing water. The bioproduct was used either sonicated or non-sonicated and two volumes of mixing fluid were tested. The aim was to assess the advantages and drawbacks that could be achieved with a waste-based bioproduct, instead of petrochemical-based additions. The investigation revealed a positive effect on workability, producing mortars with a lower mixing fluid content, improving the mechanical performance. Finally, the bioproducts reduced the mortar water absorption by gravity and capillary.